Narrating the pain and struggling against oblivion in Colombia. Recovery and institutional handling of the war wounds - Jaramillo Marín, Jefferson (Sociedad y Economía, 2010)
The article examines different experiences of recovery and institutional handling of the wounds of the Colombian war. Its objective is to identify how in various joints of the national history, it creates “study commissions of violence” allowing the one hand, the historical reconstruction of the causes, course and consequences of armed conflict, and secondly, bleeding production and narrative memories against forgetting. Throughout the text, we highlight several of these experiences, which take place between 1958 and 2006 in the midst of a “war without transition”. Then, we identify the core domains that are involved in the recovery of historical memory in the process of Justice and Peace, in particular the work of the Area Historical Memory.